Design and implementation of balanced scorecard in a multinational company - Case study - Paukku, Arto (My University, 2007)
This thesis is a constructive case study, in which the focus is to design and implement a performance measurement system according to the balanced score-card (BSC) model. Three major strategic goals of the case company consisting of four countries are divided to various internal strategic initiatives and the devel-oped balanced scorecard presents the current stage of the successfulness of the initiatives and therefore the fulfillment of the corporate strategy. Three strategic initiatives were chosen as pilots, and the performance measures for those were designed and implemented with the top level management and responsible managers of the initiatives. The researcher was a part of the BSC project team, which had the operative responsibility of the design and implementation of the new performance measurement system. The scientific significance value of this thesis is the design and implementation of BSC to a multinational company, and the modified design, implementation, and use process developed during the BSC project. Problems and other observations in the different phases of the design and implementation are documented to create practical and scientific information about the relevant characteristics concerning the implementation of BSC to a multinational company. The thesis consists of a theory part and a case study part, where the designed and implemented performance measurement system is introduced. The appli-cability of the BSC is statistically tested in the case part. The results indicate that the developed BSC is a functioning tool of management control system, and it is considered better than the previous measurement system concerning strategic measurement. The case organization is a non-manufacturing subsidiary com-pany operating in Finland and in the Baltic countries.
Keywords: performance measurement; performance measurement system; performance measure; balanced scorecard; design and implementation; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|